Phytonutraceutical evaluation of five varieties of tomato (Solanum lycopersicum) during ripening and processing - Vega Lopez, Brainer (2022)
Tomato (Solanum lycopersicum) is the largest produced vegetable in the world after potato and sweet potato. It is an important source of carotenoids (mainly lycopene), ascorbic acid, and phenolic compounds. In this work, we evaluated five tomato varieties grown in Costa Rica, during ripening, by their capacity to produce the compounds mentioned above and their antioxidant and antimicrobial activity. Additionally, we evaluated the decay of the content of metabolites during the agro-industrial processing and the revalorizing of agricultural byproducts from the tomato industry, as sources of antioxidant compounds. The JR variety shows the highest lycopene concen- tration, 243 ± 7 μg/g, while the highest concentration of this metabolite in the paste corresponded to variety 1710 with a value of 238 ± 7 μg/g. Variety 115 showed the highest concentration of carotenoids in fresh fruit, post-harvest fruit, and tomato paste (4.1 ± 0.6, 2.42 ± 0.08, and 1.84 ± 0.01 mg/g, respectively). The highest content of total phenols was obtained in leaves of the 115 variety, with a concentration of 9.0 ± 0.2 mg GAE/ gDS. We also demonstrated that leaves are a valuable source of phenolic antioxidants. Additionally, there is a demonstrated antimicrobial capacity in some ethanolic extracts of tomato, and the spectrum of action depends on the variety and the ripening of cherry-type varieties